Beyond the Intestinal Celiac Mucosa: Diagnostic Role of Anti-TG2 Deposits, a Systematic Review - Gatti, Simona; Rossi, Matilde; Alfonsi, Simona; Mandolesi, Alessandra; Cobellis, Giovanni; Catassi, Carlo (Frontiers in Medicine, 2014)
Abstract Aim: to review the existing literature on the role and significance of intestinal transglutaminase 2 IgA deposits (TG2 deposits) in patients with overt CD, potential CD and other autoimmune or gluten-related conditions. Methods: we conducted a systematic review of studies published in English, evaluating presence and characteristics of TG2 deposits in subjects with overt CD, potential CD (PCD), gluten-related diseases (Dermatitis Herpetiformis, Gluten-Ataxia), autoimmune disorders (Type-1 Diabetes) and other conditions. Studies were identified through a MEDLINE search (1950-2013). Results: twenty-three studies were included in the review. Eleven studies were performed in children. Overall TG2 deposits were present in 100% of adults with overt CD, while in children prevalence ranged from 73.2% to 100%. Six studies with an established definition of PCD were considered, prevalence of deposits ranging from 64.7% to 100%. A single study followed-up PCD patients with repeated biopsies and identified presence of intestinal deposits as the best marker to reveal progression towards villous atrophy. Two studies investigated presence of deposits in Dermatitis Herpetiformis (DH), reporting a prevalence between 63 and 79%. A single study documented TG2 deposits in 100% of patients with gluten-ataxia (GA). In children with type-1 Diabetes (T1D) positivity of intestinal TG2 deposits ranged from 25 to 78%. Conclusion: TG2 deposits seem to be a constant feature in overt CD patients and are frequently detectable in other gluten related conditions (DH and GA). The vast majority of PCD patients express TG2 deposits at the intestinal level, but no sufficient data are available to exactly define their prognostic role as a marker of evolution toward overt CD. The frequent finding of TG2 deposits in the intestinal mucosa of patients with T1D is an interesting observation deserving further evaluation.